A 9-year evaluation of temporal trends in alosetron postmarketing safety under the risk management program. (September 2013) - Tong, Kenneth; Nicandro, Jean Paul; Shringarpure, Reshma; Chuang, Emil; Chang, Lin
Objectives: Adverse events (AEs) of ischemic colitis (IC) and complications of constipation (CoC) associated with alosetron are rare and have been adjudicated during the first 5.5 years of the risk management program (RMP); however, changes in incidence rates relative to reductions in AE reports and increases in alosetron prescriptions over the 9-year RMP have not been evaluated. The authors aim to evaluate temporal trends in alosetron postmarketing safety over the 9-year RMP. Methods: The alosetron safety database was searched to identify cases of IC, CoC, and related AEs from 20 November 2002 to 31 December 2011. Adjudication of IC and CoC cases were based on US Food and Drug Administration-defined criteria. Incidence rates were calculated using the number of AEs and alosetron prescriptions (expressed as cases/1000 patient-years exposure). Results: A total of 29 cases were adjudicated as probable/possible IC and 7 cases were adjudicated as CoC. Cumulative adjudicated incidence rate of IC (1.03 cases/1000 patient-years) is low and stable, while that of CoC (0.25 cases/1000 patient-years) is low, declining progressively over time. Decreases in the incidence rates of potential symptoms of IC (abdominal pain with bloody diarrhea/hematochezia) and CoC (constipation) were also observed. Conclusions: Over the 9-year RMP period, incidence rates of IC and CoC remain rare. Substantial reductions over time were observed in the incidence of CoC and in symptoms suggestive of IC or CoC, while IC incidence has been stable at approximately 1.0 case/1000 patient-years. Decreases in AEs and serious outcomes associated with IC and CoC since the reintroduction of alosetron are likely attributable to the RMP.